THE CHEMICAL COMPOSITION OF FRESH GREEN SEAWEED (Caulerpa lentillifera ) - Santika, Jesi; Sukmiwati, Mery; Diharmi, Andarini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT Seaweed is a food raw material for aquatic products with high nutritional content. One species of green seaweed is Caulerpa lentillifera. The advantages of the chemical composition of C. lentillifera are high carbohydrate content, but low fat content and can be developed as a functional food. This study aimed to determine the chemical composition of fresh green seaweed (C. lentillifera). The research method of seaweed preparation by cleaning from all impurities produced sea grapes that were free from all impurities. Sea grapes are reduced in size to analyze their chemical composition. The analysis parameters consisted of moisture, ash, protein, fat, and carbohydrate (by different) content. The results showed that the chemical composition of fresh green seaweed (C. lentillifera) consisted of moisture 92.02% (ww), ash 44.75% fat 7.08%, protein 13.64%, and carbohydrates 16.40% (dw). The chemical composition of sea grapes is mostly ash content (minerals) and carbohydrates.Keywords: chemical composition, ash, carbohydrate